Climate policy, asymmetric information and firm survival - Cathrine Hagem (Fondazione Eni Enrico Mattei (FEEM), 2001)
The purpose of this paper is to compare the effect of different domestic climate policy instruments under asymmetric information when the regulator wants to secure the survival of a specific firm. It is a well-known result from economic theory that emission taxes lead to a cost-effective distribution of abatement across polluters. However, if the regulator wants to ensure the survival of a specific firm, it may need to design policy instruments that reduce the firm's cost of complying with an emission tax regime. The climate policy instruments considered in this paper are tradable emission permits with distribution of free permits, emission taxes in combination with a fixed subsidy, and two types of voluntary agreements. It demonstrates first that if distributing free tradable permits shall have a preventing effect, the allocation of permits has to be made contingent on production. It further shows that a voluntary agreement where a specific abatement target is set by the regulator can prevent a shutdown but leads to lower welfare than the use of emission taxes in combination with a fixed subsidy. And finally it illustrates that a voluntary agreement designed as a menu of abatement contracts increases social welfare compared to an emission tax regime.
Keywords: D82; Q25; 330; Climate policy; tradable permits; emission taxes; voluntary agreements; asymmetric information; Klimaschutz; Ökosteuer; Emissionshandel; Selbstverpflichtung; Asymmetrische Information; Theorie